Are there economic returns from democracy? : the experience of Sub-Saharan Africa from 1988-2007 - Andersen, Ryan (Department of Political Studies, 2015)
There is an enduring debate as to whether democracy promotes or hinders economic growth. This study examines the relationship between democracy and economic growth in 47 sub-Saharan African countries from 1988 to 2007. From the late 1980s until the mid-1990s, a period of democratization swept the continent. This period of democratization was followed by a period of strong economic growth from the mid- 1990s through 2007. It is argued here that these events are not coincidental and that democracy is advantageous to economic growth, particularly in the sub-Saharan Africa region. Using statistical analyses such as bivariate correlation and multiple regression, the relationship between democracy and economic growth is examined using a number of control variables to test the strength of the relationship between democracy and growth. To date, the empirical research on democracy and economic growth provides conflicting results, ranging from positive to negative to neutral effects. The results of this study show that there is a correlation between higher levels of democracy and higher levels of economic growth during certain periods. However, this relationship weakens to levels that are not significant once certain combinations of control variables are included. While the results of the study do not provide a definitive answer to the debate, they do refute certain arguments that have been made about the main drivers of economic growth in the region. The results also show that democracy does not have a negative effect on growth, which highly suggests that there might be a sequence effect involved in the path towards democratization and economic growth.